2019
DOI: 10.5324/nordis.v0i26.3294
|View full text |Cite
|
Sign up to set email alerts
|

Time Development of Voltage Frequency Dependence of Partial Discharge Activity in Voids

Abstract: Condition assessment of high voltage equipment based on partial discharge measurements is often performed after a voltage pre-conditioning period. The aim of this paper is to present results from experimental examinations of time variance of partial discharge activity and to propose physical explanations of the phenomena observed. Experiments were performed on laboratory made 3 mm thick discs of generator bar insulation, consisting of mica and glass fiber reinforced epoxy with a 0.5 mm thick cylindrical void s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…The total apparent charge during the 5 s conditioning between the different frequencies generally increased with time. This indicated that the preconditioning effect faded with time, similarly to what was seen in [16]. This means that the effect of preconditioning was weaker at lower frequencies than at higher frequencies due to the frequency test order.…”
Section: Influence On Pdiv Fromsupporting
confidence: 56%
See 2 more Smart Citations
“…The total apparent charge during the 5 s conditioning between the different frequencies generally increased with time. This indicated that the preconditioning effect faded with time, similarly to what was seen in [16]. This means that the effect of preconditioning was weaker at lower frequencies than at higher frequencies due to the frequency test order.…”
Section: Influence On Pdiv Fromsupporting
confidence: 56%
“…The effect of such preconditioning disappears with time [16]. Generally, at elevated temperatures, the PD byproducts diffuse or are neutralised faster than they are produced.…”
Section: Void Voltage Modelsmentioning
confidence: 99%
See 1 more Smart Citation